Rancang Bangun Sistem Informasi Inventory Metode Fifo (First In First Out) Pada Toko Bangunan Intilogam - Parindo, Kevin; Hadinata, Novri (LPPM STIKOM Tunas Bangsa, 2024)
The inventory information system is a digital platform specifically designed to manage inventory in real-time. With the rapid advances in technology, business actors are encouraged to adapt and utilize technology to support accelerated business growth. Intilogam building shop is a building shop that provides various kinds of building and construction materials. The process of managing inventory at the Intilogam building shop is still carried out conventionally, with this process having several shortcomings such as loss of documents, damage to documents, and errors in recording the amount of inventory. To support an efficient inventory management process, the author designed and built a website-based FIFO (First In First Out) inventory information system. The method the author uses in building the system is Extreme Programming (XP), this research was carried out at the Intilogam building shop. This inventory information system helps make it easier for Intilogam building shop owners to manage inventory, minimizes damage and loss of inventory recording documents, and makes it easier for Intilogam building shop owners to access inventory reports anytime and anywhere.